Role of closed subcutaneous drain in prevention of surgical site infection in perforation peritonitis - Raj, Praveen L.; Ranjan, Alok; Kumar, Ajay; Thakur, Indra Shekhar (International Journal of Research in Medical Sciences, 2023)
Background: Surgery for perforation peritonitis is associated with the highest rates of infective complications, especially surgical site infection. SSI occurs due to failure of obliteration of dead space during abdominal wound closure resulting in formation of hematoma and seroma collection in the surgical wound viz. abdominal wound in cases of perforation peritonitis. This acts as a good culture medium for bacterial organisms to grow and cause wound infection. The bacterial pathogens can be either from intra-abdominal sepsis or nosocomial in origin. Closed suction drains can be used effectively to eliminate dead space in the wound and evacuates the seroma or hematoma collection, thereby reducing chances of SSI and also helps in early detection of SSI by inspecting the nature of drain output. Aim was to evaluate the role of closed suction drains in prevention of SSI in cases of perforation peritonitis. Methods: Comparative study of 60 cases of perforation peritonitis divided into two equal groups (Group A patient with closed suction drain in subcutaneous space vs. Group B patient without closed suction drain). Outcomes of SSI were compared. Results: The incidence of SSI in Group A was 33% whereas in Group B was 70%. 40% cases in SSI in Group A whereas 76% cases of SSI in Group B developed wound dehiscence. Most cases of SSI was diagnosed on POD 2 for Group A and on POD 4 for Group B. Conclusions: The study supports use of closed suction drain in perforation peritonitis for prevention, early detection and appropriate management of SSI.